ChemInform Abstract: Transition‐Metal Free Oxidative Aliphatic C—H Fluorination. Issue 44 (15th October 2015) - Zhang, Xiaofei; Guo, Shuo; Tang, Pingping
Abstract An efficient, metal‐free fluorination is presented.